Event Management Strategy Of Narawandira Temporary Exhibition At Ngayogyakarta Hadiningrat Karaton In 2023 - Yoga Harfa Pangestu; Angga Intueri Mahendra P (PT Mattawang Mediatama Solution, 2023)
Management strategy is an importantl part of an organization, involving decision-making plans that utilize available resources to achieve the established vision and objectives. This research was conducted due to an interest in the management process of the temporary exhibition